Building Information Modelling (BIM): A Narrative Literature Review on Theory, Benefits, and Barriers - Jalaludin (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2025)
Building Information Modelling (BIM) has emerged as a transformative methodology within the Architecture, Engineering, and Construction (AEC) sector, significantly changing the approach to project planning, execution, and management. This study presents a narrative literature review (NLR) of BIM, focusing on its theoretical foundations, implementation benefits, and the key barriers to its adoption. The objective is to identify and synthesize the core concepts that define BIM's maturity levels, level of development (LOD), and the use of a common data environment (CDE) within the construction industry. The literature search was conducted using Google Scholar, with keywords such as